Pengaruh FoMO (Fear of Missing Out) pada Generasi Z Terhadap Ketakwaan Kepada Allah SWT. - Septia Wardani, Diah Sinta; Cahyani, Resita (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2023)
In the digital era like today, social media is one of the impacts of the increasingly advanced times and technology that is currently developing. Social media has become a mandatory asset that must be owned by every human being in the world, from toddlers to parents. Of course, with every innovation that is raised, there is an impact that follows, whether it's negative or positive. Making it easy to communicate remotely is one of the positive effects of social media. Meanwhile, one of the negative impacts is a psychological disturbance that has recently been rife, namely FoMO (Fear of Missing Out). FoMO (Fear of Missing Out) arises due to feelings of anxiety, worry, and fear of our absence in the moments that are happening around us. In Islam itself, FoMO (Fear of Missing Out) has been explained long ago by Allah SWT. in the holy book Al - Qur'an, one of which is contained in Qs. Al- Baqarah: 155 explains that Allah SWT. will test His servant with a little fear, hunger, lack of wealth, soul, and fruit. So that with the notification from Allah SWT. generation Z can always be vigilant and always ask for protection from Allah SWT. from any impact caused by social media.